CSR Themes Quality, Good Corporate Governance, and Earnings Management: Evidence from Indonesia - Andrian, Tommy; Murwaningsari, Etty (International Journal of Sustainable Development & World Policy, 2021)
The study aims to investigate the effect of CSR themes quality on earnings management. The paper also examines the moderating effect of good corporate governance on the relationship between CSR themes quality and earnings management. The study uses a quantitative approach and panel data regression using 170 firm-year observations of consumer goods industries listed in IDX for 2015-2019. This study uses the measurement of the CSRD using a combined corporate social responsibility matrix from three countries and examining each theme (environment, energy, human resources, community development, other CSR activities) in CSR to know which pieces are involved can reduce EM practice. The result suggests product & innovation and community development have a negative and significant influence on earnings management. This research also shows that the positive effect of community development and others CSR activities on earnings management is strengthened with good corporate governance. This proves that companies with higher earnings management levels use CSR activities to disguise opportunistic managerial behavior. Still, companies that make disclosures on product & innovation and community development activities can limit their earnings management. Then, the implementation of GCG, which is related to transparency, will cause less motivation to practice earnings management.